Power Quality Analysis of a Microgrid-Based on Renewable Energy Sources: A Simulation-Based Approach - Emmanuel Hernández-Mayoral; Christian R. Jiménez-Román; Jesús A. Enriquez-Santiago; Andrés López-López; Roberto A. González-Domínguez; Javier A. Ramírez-Torres; Juan D. Rodríguez-Romero; O. A. Jaramillo (Computation)
At present, microgrids (μGs) are a focal point in both academia and industry due to their capability to sustain operations that are stable, resilient, reliable, and of high power quality. Power converters (PCs), a vital component in μGs, enable the decentralization of power generation. However, this decentralization introduces challenges related to power quality. This paper introduces a μG model, based on the IEEE 14-bus distribution system, with the objective of investigating power quality when the μG is operating in conjunction with the conventional power grid. The μG model was developed using MATLAB-Simulink®, a tool specialized for electrical engineering simulations. The results obtained undergo thorough analysis and are compared with the compatibility levels set by the IEEE-519 standard. This method enables a precise evaluation of the μGs’ capacity to maintain acceptable power quality levels while interconnected with the conventional power grid. In conclusion, this study contributes significantly to the field of μGs by providing a detailed and quantitative assessment of power quality. This will assist in the design and optimization of μGs for effective implementation in real-world electric power systems.